1992
DOI: 10.1007/bf01191504
|View full text |Cite
|
Sign up to set email alerts
|

Myelination of regenerated axons in goldfish optic nerve by Schwann cells

Abstract: This study uses immunohistochemistry and EM to examine the site of injury in goldfish optic nerve during axonal regeneration. Within seven days of nerve crush axons begin to regrow and a network of GFAP+ reactive astrocytes appears in the nerve on either side of the injury. However, the damaged area remains GFAP-. By 42 days after nerve crush, the sheaths of new axons acquire myelin marker 6D2, and the crush area becomes populated by a mass of longitudinally-orientated S-100+ cells. Ultrastructurally, the pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0
5

Year Published

1994
1994
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 47 publications
2
18
0
5
Order By: Relevance
“…It is most likely that these cells represent peripheral macrophages, which were recruited to the site of the crush (Blaugrun et al, 1992;Lawson et al, 1994;Zeng et al, 1994;Podhajsky et al, 1997) and were responsible for the rapid, effective clearance of the lesion by 2 weeks postoperative (see also Levine, 1991;Nona et al, 1992). Interestingly, the segment of the nerve that was closest to the lesion, the distal segment, was also cleared relatively rapidly compared to the more distant cranial segment.…”
Section: Discussionmentioning
confidence: 90%
“…It is most likely that these cells represent peripheral macrophages, which were recruited to the site of the crush (Blaugrun et al, 1992;Lawson et al, 1994;Zeng et al, 1994;Podhajsky et al, 1997) and were responsible for the rapid, effective clearance of the lesion by 2 weeks postoperative (see also Levine, 1991;Nona et al, 1992). Interestingly, the segment of the nerve that was closest to the lesion, the distal segment, was also cleared relatively rapidly compared to the more distant cranial segment.…”
Section: Discussionmentioning
confidence: 90%
“…Because none of the antibodies against laminin that we tested binds to goldfish nervous system, we were unsuccessful in resolving this issue. Nona et al (1992) reported that Schwann cells invade the optic nerve when the nerve is crushed and may, due to their favorable substrate properties, assist the regrowth of axons. In collaboration with Samual Nona, we were able to exclude the possibility that Schwann cells invade and populate the optic nerve when the nerve is cut instead of crushed (Bastmeyer and Nona, unpublished results).…”
Section: Discussionmentioning
confidence: 99%
“…We describe their organization by using immunohistochemistry (IHC) and electron microscopic analyses and we look for some differences with the glial cells located in the ONH of mammals. We used anti-S100 and anti-GFAP antibodies, previously used in the visual system of teleosts, to identify glial cells (Dahl et al 1985;Maggs and Scholes 1986;Levine 1989;Nona et al 1989Nona et al ,1992Vecino et al 1997;Velasco et al 1997;Jimeno et al 1999). We employed anti-PCNA (Bravo et al 1987) to analyze the proliferative potential of a population of possible glial cell precursors that we detected in the intraocular portion of the ONH.…”
mentioning
confidence: 99%